Pembangunan Aplikasi Cross-Platform Pelacak Kendaraan dengan Metode Portable Class Library (Studi Kasus Perusahaan Laundry Taptopick) - Albilaga Linggra Pradana; Komang Candra Brata; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the factors which can keep a company to running theirs smoothly is the ability to maintain customer loyalty. On a new company, maintaining loyalty is not easy to do because there are several factors that must be addressed. There is a tranportation company that succeeds in maintaining loyalty which is always use business support technology that is intended to focus on the responsibilities of each fleet of drivers. This technology is beneficial for the cost efficiency that customers can feel. Therefore, the case study in this study is on a company that still has employee performance problems that is Taptopick company that serves laundry on-demand in Jakarta. The problem is the difficulty of monitoring the work performed by employees which can causing some problems such as spend too much times of order pickup process which can result in customer disappointment. Based on this problem, this study will design and build a vehicle tracking application which can installed in various operation systems owned by couriers by utilizing cross-platform technology with portable class library method. The results of this research are the list of functional and non-functional requirements of the application, designs models and explanation of how this is implemented. Then for usability testing of the implementation in building the Vehicle Tracking Application was obtained satisfactory results with an average above the standard that is 83,33.